2019
DOI: 10.2478/enr-2019-0010
|View full text |Cite
|
Sign up to set email alerts
|

Clozapine impact on FosB/ΔFosB expression in stress preconditioned rats: response to a novel stressor

Abstract: Objective. Prolonged treatment with neuroleptics has been shown to induce FosB/ΔFosB expression in several brain regions including the medial prefrontal cortex, dorsomedial and dorsolateral striatum, ventrolateral and dorsolateral septum, nucleus accumbens shell and core, and the hypothalamic paraventricular nucleus (PVN). Some of these regions are known to be also stress responsive. This study was designed to determine whether repeated clozapine (CLZ) administration for 7 consecutive days to Wistar rats may m… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1

Citation Types

0
2
0

Year Published

2020
2020
2023
2023

Publication Types

Select...
2

Relationship

1
1

Authors

Journals

citations
Cited by 2 publications
(2 citation statements)
references
References 32 publications
(38 reference statements)
0
2
0
Order By: Relevance
“…These proteins are transcriptional factors and exert their effects by enhancing or repressing the expression of other genes and are involved in the development and maintenance of anxiety and nociception. In general, acute stress increases c-Fos and FosB expressions in the PVN [ 58 , 59 ], whereas the effect of chronic stress on c-Fos and FosB expressions seems to be bidirectional [ 60 , 61 , 62 ]. Evidence demonstrated that chronic psychological stress alone decreased c-Fos expressions [ 61 ], while antipsychotic drug treatment increased c-Fos expressions in the PVN [ 63 ].…”
Section: Discussionmentioning
confidence: 99%
“…These proteins are transcriptional factors and exert their effects by enhancing or repressing the expression of other genes and are involved in the development and maintenance of anxiety and nociception. In general, acute stress increases c-Fos and FosB expressions in the PVN [ 58 , 59 ], whereas the effect of chronic stress on c-Fos and FosB expressions seems to be bidirectional [ 60 , 61 , 62 ]. Evidence demonstrated that chronic psychological stress alone decreased c-Fos expressions [ 61 ], while antipsychotic drug treatment increased c-Fos expressions in the PVN [ 63 ].…”
Section: Discussionmentioning
confidence: 99%
“…Actually, the c-Fos and related gene products belong to the transcription factors candidates that could create linkage between the acute cell surface receptor occupancy by APs and the gradual, long-lasting neural changes induced by their chronical treatment (Hiroi and Graybiel 1996). The long-lasting effect induced by APs repeated treatment can be monitored by the deltaFosB (ΔFosB), expression, a truncated splice variant of the FosB/ΔFosB gene (Kovacs 1998;Majercikova and Kiss 2015;Majercikova et al 2016;Kiss and Majercikova 2017;Osacka et al 2019). The functional significance of ΔFosB has been implicated in different experiments.…”
mentioning
confidence: 99%